Investigating Factors Effect on Fruit and Vegetable Consumption: Applying Social Cognitive Theory - Mostafa Nasirzadeh; Mahdi Abdolkarimi; Zahra Asadollahi; Maryam Hashemian (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: Regular fruit and vegetable consumption is one of the most important and preventative indicators for the development of obesity, disorders, and diseases.The aim of this study was to identify the determinants of fruit and vegetable consumption based on social cognitive theory among first-grade high school female students. Methods: This descriptive cross-sectional study was performed on 264 high school female students who were selected through multistage random sampling from school students in Rafsanjan. The data were collected through a demographic questionnaire, the seven-day fruit, and vegetable consumption frequency, and the fruit and vegetable consumption determinants questionnaire that was developed based on the constructs of cognitive social theory. Then were analyzed using SPSS-16 software through independent samples t-test, Pearson correlation, one-way ANOVA, and multiple linear regression analysis. Results: The average daily fruit and vegetable intakes in adolescent girls were 3.43 and 2.30 units per day, respectively. The results of multiple regression analysis showed that environmental factors and behavioral skills have a significant relationship with fruit consumption. Besides, vegetable consumption was found to have a significant relationship with behavioral skills and social reinforcement (P <0.05). In sum, the constructs of social cognitive theory explained 7.1% of the variances in fruit consumption and 9.8% of the variances in vegetable consumption. Conclusion: The average daily fruit and vegetable intakes were less than the recommended level. It is recommended that further interventional studies be designed in order to explore environmental factors and behavioral skills based on the constructs of social cognitive theory.